Peningkatan Hasil Belajar Siswa Dengan Menggunakan Berbasis Tekhnologi di UPTD SDN 05 Sialang - Indra Leni; Iswantir Iswantir; Defi Yuslia; Amrina Amrina; Peta Mayurida; Victoria Lilian (Jurnal Pendidikan Tuntas, 2024)
This research is motivated by the low learning outcomes of students in the grade IV children at UPTD SDN 05 Sialang. One solution to this problem is to implement activities using the Technology Based, this study aims to improve the learning outcomes of children in Grade IV UPTD SDN 05 Sialang. The method used in this study is the Classroom Action Research (CAR) method. This classroom action research was carried out in 2 cycles, each cycle had 2 meetings. The data collection techniques used were observation and documentation. The results of this study show an increase in children's grades from pre- action, cycle I and cycle II which can be clearly described as follows: BB grades in pre-action were 10 children or 70%, then in cycle 1 it became 6 children or 40%, then in cycle II it became 1 child or 10%. Based on the results of the study above, the researcher suggests that teachers use the Make a Match method as an alternative activity in improving children's learning outcomes. Keywords: , T,